Increased Interest and Ability to Identify Types Of Work That Produce Goods Through The Use Of The Discussion Method and Image Media In Class 3 Semester 2 SDN 02 Tegalsari - Sya’diyah, Siti Halimatus (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The aim this research to improve learning outcomes in learning Social Science Basic Competencies of types of work with discussion methods and image media in class III SD Negeri 02 Tegalsari, Ampelgading District, Pemalang Regency. The research was carried out in two cycles, namely Cycle I was held on Wednesday, February 26, 2020 and Cycle II was held on Tuesday, March 10, 2020. Each cycle consisted of four stages, namely planning, implementation, observation and reflection. The subjects of this class action research are third grade students of SDN 02 Tegalsari. Learning outcomes in this study have increased after using the discussion method and picture media, as indicated by the completeness score of 30 students, 27 or 90% of students completed the study with the Minimum Completeness Criteria (KKM) of 70. In the previous study only 14 or 47% of students who complete in learning. Thus the use of discussion methods and media images can improve learning outcomes of Social Sciences.